Coronary Angiographic Findings in Diabetic Patients Versus non-Diabetics with Coronary Heart Disease - Kadhim, Akram Rasol; Strak, Sarkis K.; Hazaa, Mazin A. (AL-Kindy College Medical Journal, 2013)
Background :Atherosclerosis is the mostfrequent underlying cause of ischemic heartdisease and a major cause of death all over theworld. This study was carried out to analyze andcompare the angiographic findings in patientswith diabetes mellitus versus non diabetics withcoronary heart disease , and to correlate thesefindings with some risk factors for coronaryheart disease.Methods: A total of 100 patients were studied,50 with diabetes mellitus, and 50 non diabetics.This study was carried out at Al-Sadr teachinghospital in Basrah, Southern Iraq during theperiod April 2009- September 2009. All patientswere known to have coronary heart disease. Riskfactors for coronary heart disease were studiedand coronary angiography was performed todefine coronary lesions for all patients, and wereclassified into those who had single , two , threeor four vessels disease, according to the numberof critical coronary vessels involed. Angiographywas considered as normal when the test did notidentify any obstruction of any major epicardialartery.Results: Diabetic patients had more multi-vesselsinvolvement coronary heart disease than nondiabetics. Right coronary artery, left main stemartery, left circumflex artery involvement and leftventricular systolic dysfunction were seen morein diabetics than non diabetic patients.Conclusions: This study showed that diabeticpatients had more critical multi-vesselsinvolvement than non diabetic. Diabetic patientshad also worse coronary angiographic findingsindependent on the presence or absence of otherrisk factors